The influence of ambience and social interaction on young adults' intention to patronize coffee shops / Aliya Omar and Putri Dahlia Ab Rashid - Omar, Aliya; Ab Rashid, Putri Dahlia (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Due to the enormous increase of independent café establishments over the past few years, the coffeehouse industry is currently characterised by severe competition. This is a result of the fact that there is an increase in frequent visits to coffee shops among young individuals. The current study demonstrates that a variety of characteristics, such as the coffee shop's ambience and social interaction, influence customers' decisions to frequent them. The purpose of this study is to determine what factor encourages customers to return to a coffee shop. This study specifically looks at the effect of ambience and social interaction on customer behaviour at neighbourhood coffee shops. Young adults between the age of 18-29 years old in Kuching, Sarawak, were the focus of this investigation. This study included a sample of 370 people who were coffee shop customers. Descriptive statistics, reliability analysis, Pearson's Correlation, and Multiple Regression Analysis were utilized to analyse the collected data. The results meet the research objectives: to identify the relationship between two variables (ambience and social interaction) towards the intention to patronage coffee shops. The study's findings generally demonstrated that both social interaction and ambience had a significant and favourable impact on customers' intentions.